KCNJ11 MUTATIONS CAUSE SEVERE NEUROPSYCHOLOGICAL DEFICITS. Issue 12 (15th November 2016) - Day, Jacob; Torrens, Lorna; Bowman, Pamela; Shepherd, Maggie; Chakera, Ali; Hattersley, Andrew; Zeman, Adam
Abstract : Background/Aims: KCNJ11 encodes Kir6.2, the pore-forming subunit of the ATP-sensitive potassium channel present in brain regions including the hypothalamus, neocortex and cerebellum. Its neurological function is uncertain. KCNJ11 activating mutations cause neonatal diabetes (ND) as it is also expressed in the pancreas. This provides a unique opportunity to study the role of the channel in the human brain. We evaluated the neuropsychological features in patients with ND due to KCNJ11 mutations. Methods: Six cases with KCNJ11 mutations and a developmental phenotype were evaluated by a neurologist and a neuropsychologist and compared with three controls with ND due to mutations in the INS gene, which is expressed only in the pancreas. Results: Median IQ was 65 (cf 99 in controls, P<0.05). Visuospatial and executive domains were particularly affected. Autistic features were present in five cases but none of the controls (p<0.05). One case had mild chorea; three of four testable cases showed dyspraxia and motor sequencing difficulties. Conclusions: KCNJ11 mutations can cause a severe neuropsychological phenotype with intellectual disability, impaired visuospatial and executive abilities, and autistic features. This suggests a role for the K-ATP channel in brain development and channel dysfunction may be important in the pathogenesis of neurodevelopmental disorders.